Energy Dissipation Characteristics and Dynamic Modeling of the Coated Damping Structure for Metal Rubber of Bellows - Kenan Wu; Hongbai Bai; Xin Xue; Tuo Li; Min Li (Metals, 2018)
A novel coated damping structure for metal rubber (MR) of bellows is designed based on large-size metal rubber sheets. This structure is dynamically tested in the bending direction at normal temperature. According to the test results, a model of the nonlinear elastic restoring force is set up, which describes the dynamic characteristics of the coated damping structure for metal rubber of bellows, and identifies the parameters of the model. The results show that the coated damping structure for metal rubber of bellows has a strong damping energy dissipation ability, its dynamic vibration characteristics are related to the vibration amplitude and frequency, and it is a complex nonlinear hysteretic system with multiple damping components. After identification of the parameters, the model of nonlinear elastic restoring force shows highly accurate results.